A three-level universal electric vehicle charger based on voltage-oriented control and pulse-width modulation - Al-Ogaili A.S.; Bin Aris I.; Verayiah R.; Ramasamy A.; Marsadek M.; Rahmat N.A.; Hoon Y.; Aljanad A.; Al-Masri A.N. (MDPI AG, 2023)
Charging time; Controllers; Digital signal processors; Electric vehicles; Harmonic analysis; Harmonic distortion; MATLAB; Pulse width modulation; Renewable energy resources; Voltage control; Wave filters; Decoupled controller; Digital signal processors (DSP); Non-renewable energy resources; Sinusoidal pulse width modulation; Three-level; Total harmonic distortion (THD); Utility distribution system; Voltage oriented control; Secondary batteries